STRATEGI PENGEMBANGAN PADA KAWASAN WISATA GUNUNG KELUD DI KECAMATAN NGANCAR, KABUPATEN KEDIRI - Trimelia Anggraini; Herbasuki Nurcahyanto; Aufarul Marom (Journal of Public Policy and Management Review, 2023)
Mount Kelud Tourism Area is one of the tourism potentials in Kediri Regency, with special potential in the form of a natural tourism area with views of an active volcano which has a unique form of a mountain crater. However, until now the development of the Mount Kelud Tourism Area has not run optimally. Not a few visitors or local people who participate in tourism activities complain, especially about the lack of various infrastructure facilities in tourist areas. This is of course very much related to the development side itself which also has various obstacles. This study aims to analyze the current conditions in the Gunung Kelud Tourism Area and formulate a development strategy based on an analysis of the internal and external environment. This study uses the theory of strategic planning put forward by John. M. Bryson, using descriptive qualitative research methods with SWOT analysis techniques and Litmus Tests to formulate the right strategy. The results of this study indicate that the development that has been carried out by the Tourism and Culture Office of Kediri Regency has been endeavored to run as it should, but there are still many things that need to be improved. Then, the results of the SWOT analysis found 11 development strategic issues, which after the litmus test obtained 8 issues with a strategic nature, 3 of which had the highest score that could be applied in development. Suggestions from research are the need to increase cooperation with various parties starting from the utilization of land availability; development of infrastructure facilities; management and maintenance of tourist attractions; expand the promotion network; community participation through the formation of Pokdarwis; making tour packages; economic improvement by utilizing the availability of places that are not yet operational; and disaster mitigation is also needed as a preventive measure.